The Use of Classmates as a Self-Motivation Strategy From the Perspective of Self-Regulated Learning - Suárez, José Manuel; Fernández, Ana Patricia; Zamora, Ángela (Frontiers in Psychology, 2019)
It can be stated that self-regulated learning (SRL) brings broad benefits to the process of students' learning and studying. However, research has yet to be undertaken in relation to one of its components, namely self-regulation of motivation and affectivity. The main objectives of this study are to examine the use of self-motivation strategies that involve classmates and to obtain models on the influence of academic goals and self-efficacy on such self-motivation strategies. To this end, was conducted a study using two different samples of students in the compulsory secondary education or baccalaureate stages in Spain (N = 613 and N = 910). The results obtained indicate that, with regard to gender, differences only exist in the use of the strategy of deception (t = 5.450, p < .001, d = .364). That the two pairs of strategies positively and significantly correlated with one another (r = .239, p < .01 and r = .355, p < .01). That only the strategy of annulation of others correlates with a more adaptive type of motivation. Thus, the group of students that reported the greatest level in its use also did so in relation to task and ego self-enhancing goals, to self-efficacy, and being negatively associated with the goal of work avoidance. Finally, were offered models on relationships between academic goals, self-efficacy and enhancement and annulation strategies (χ² (8) = 5.204, p = .736) and deception and annulation strategies (χ² (4) = 3.228, p = .520).